Synthesis and evaluation of atorvastatin esters as prodrugs metabolically activated by human carboxylesterases. Issue 3 (1st February 2016) - Mizoi, Kenta; Takahashi, Masato; Haba, Masami; Hosokawa, Masakiyo
Graphical abstract: Abstract: We synthesized 11 kinds of prodrug with an esterified carboxylic acid moiety of atorvastatin in moderate to high yields. We discovered that they underwent metabolic activation specifically by the human carboxylesterase 1 (CES1) isozyme. The results suggested that these ester compounds of atorvastatin have the potential to act as prodrugs in vivo.